Nitrogen cycling blocked in constructed wetlands: Mechanisms, developments, and challenges—A review - Yingming Liu; Hang Gao; Zhiyuan Wang; Peiquan Xue; Xiaojie Chen; Baoshan Wang; Gang Wen (Water Research X)
Constructed wetlands (CWs) are widely used for the denitrification of wastewater because of their high efficiency and low pollutant consumption. However, insufficient internal dissolved oxygen (DO) or a lack of electron donors has resulted in a blocked electron supply and acceptance process for the nitrogen removal (N-removal) process, severely restricting the N-removal efficiency of CWs. In this study, the electron transfer mechanism of the N-removal process in CWs was reviewed, and the effects of plant action and substrate adsorption on the nitrogen cycle were discussed. To address the challenge of restricted nitrogen cycling in CWs, innovative strategies such as intermittent aeration to optimize the distribution of DO, introduction of metal oxide substrates to strengthen the electron transfer efficiency, and coupled bioelectrochemical systems (BES) have been proposed to induce system electron donors and acceptors to maintain the transfer balance. In the future, further research should explore the deep synergy between CWs and BES, development of new types of CWs fillers, and overcome the effects of low temperatures, as well as to implement further intelligent monitoring and management measures to address impeded nitrogen cycling in CWs and enhance the potential of the application of CWs in the field of wastewater denitrification.